Improved Fuzzy Evaluation Model Analysis of Nuclear Power Plant Operational Safety Performance - Dongxiao Niu; Zongyun Song; Jinpeng Liu (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The evaluation on nuclear power plant operational safety performance had great significance on whether the nuclear power plant operated safely or not. Currently the academic literatures on nuclear power plant operational safety performance are rare. Improved Fuzzy evaluation model which introduce confidence level had been used into the evaluation of nuclear power plant operational safety performance. The article built safety performance indicator system and further established importance level evaluation matrix which showed the indexes relative importance, and established performance evaluation matrix which represented indicators impact on operational effect. From the importance level evaluation matrix the weigh and confidence of indicators can be gained and from the performance evaluation matrix the evaluation matrix can be gained. The preliminary evaluation result and synthetic confidence can be obtained by multiplying evaluation matrix by indicator weigh and confidence, and then the final evaluation result can be achieved. DOI: http://dx.doi.org/10.11591/telkomnika.v12i6.5389